Interleukin-10 and Antigen-Presenting Cells Actively Suppress Th1 Cells in BALB/c Mice Infected with the Filarial Parasite Brugia pahangi - Osborne, Julie (American Society for Microbiology (ASM), 1999)
Infection with the third-stage larvae (L3) of the filarial nematode Brugia results in a Th2-biased immune response in mice and humans. Previously we have shown that the production of interleukin 4 (IL-4) is critical for down-regulating polyclonal Th1 responses in L3-infected mice. However, the in vitro neutralization of IL-4 did not fully recover the defective polyclonal Th1 responses, nor did it result in the production of any antigen (Ag)-specific Th1 cytokines, suggesting that perhaps infection with L3 does not result in priming of Th1 cells in vivo. In this study, we analyzed the role of IL-10 and Ag-presenting cells (APCs) in the spleen as additional factors controlling the Th2 bias in infected mice. Our data show that IL-10 and APCs also contribute to the suppression of mitogen-driven Th1 responses of spleen cells from infected mice. In addition, the neutralization of IL-10 or the replacement of the resident APC population from spleen cell cultures resulted in the production of Ag-specific Th1 cytokines. Irradiated spleen cells from either L3-infected or uninfected mice were able to restore Ag-specific Th1 responses in vitro. Therefore, it appears that Brugia-reactive Th1 cells are primed following infection with L3, but are actively suppressed in vivo by a mechanism that involves IL-10 and the resident APC population, but not IL-4. These results indicate that a complex interplay of cytokines and cell populations underscores the Th2-polarized response in L3-infected mice.